THE TRAGEDY OF THE SEMIPALATINSK NUCLEAR TEST SITE IN KAZAKH LITERATURE (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article examines the theme of the Semipalatinsk Nuclear Test Site and its artistic interpretation in Kazakh literature. The main aim of the study is to explore how nuclear testing has affected humanity, nature, and the spiritual world of the nation through literary works, and to identify the representation of ecological awareness in literature. The Semipalatinsk test site is viewed not only as an environmental disaster in Kazakhstan’s history but also as a global human tragedy. The analysis focuses on Rosa Mukhanova’s “The Eternal Child Image”, Mukhtar Auezov’s “Japanese Diaries”, Gabit Musrepov’s “Japanese Ballad”, and Rymgali Nurgali’s “Unfinished Tragedy”. These works artistically portray the moral, psychological, and ecological consequences of nuclear testing, emphasizing human suffering and moral responsibility. Each author connects the environmental catastrophe with national identity, spirituality, and universal humanistic values.Through comparative analysis, the study relates Kazakh literary works to global literature, including H. G. Wells’ “The World Set Free”, M. Oda’s “Hiroshima”, and F. Commoti’s scientific research. This comparison highlights both similarities and differences in how nuclear disaster is depicted in various cultural contexts.The study employs comparative, structural, and content analysis methods to reveal the relationship between ecological consciousness, collective memory, and universal values. In conclusion, literary works about the Semipalatinsk test site are seen as powerful artistic testaments that preserve historical memory, foster ecological awareness, and promote humanistic ideals.